Stretching to avoid injury - Fyfe, S.; Marshall, J.; O`Donovan, G.; Stein, A. (Peak Performance, 2008)
Stretching: A Beginner`s Guide to understanding the principles of modern stretching techniques (Sean Fyfe) Periodisation: A guide to which type of stretches are most effective and at what times of the day, week and year (James Marshall) Physiology: An intriguing insight into the do`s and don`ts of warming up, for enhanced performance and reduced injury (Gary O`Donovan) Exercises: A practical guide to dynamic stretching warm-ups, with fifteen different exercises (Alan Stein)